IDEOLOGISASI MAZHAB SYIAH DI BALIK PERIODISASI SEJARAH TAFSIR AL-QUR’AN - -, Musolli (IAIN Kediri, 2015)
This paper will examine the penetration of the ShiaÃ¢â‚¬â„¢s ideology in the periodization of the QurÃ¢â‚¬â„¢anic exegesisÃ‚Â (Tafsir). It argued that periodization phases showed the evidence of the ideologization tracing back to theÃ‚Â ShiaÃ¢â‚¬â„¢s exegetic activities by using the the theories of GramsciÃ¢â‚¬â„¢s hegemony and counter-hegemonies. This paperÃ‚Â revealed also that, as opposed to Sunni QurÃ¢â‚¬â„¢anic exegesis, the ShiaÃ¢â‚¬â„¢s QurÃ¢â‚¬â„¢anic exegesis reached its peak at theÃ‚Â period of ahl al-Bayt.Keywords: ShiÃ¢â‚¬â„¢ah, Tafsir al-QurÃ¢â‚¬â„¢an, Ideologi, Periodisasi.